An fMRI study of advertising appeals and their relationship to product attractiveness and buying intentions. Issue 6 (30th June 2016) - Chang, Hyo Jung (Julie); O'Boyle, Michael; Anderson, Ronald C.; Suttikun, Chompoonut
Abstract: This study examines the effects of various visual apparel advertisements on consumers' brain activation during exposure to different types of advertising appeals (i.e., celebrity, non‐celebrity, and rational). The influence on consumer perceptions of products and their subsequent buying intentions are also measured. A repeated measures experimental design was employed, and the total of 27 right‐handed female subjects participated in the study. The results of the quantitative data showed significant differences in perceived product attractiveness for each of the three types of advertising appeals, but not in buying intentions. Regarding the fMRI results, our findings support the notion that celebrity advertising appeals are associated with heightened brain activation of memory‐related/retrieval regions, reflecting how consumers remember the ad and are influenced by the attractiveness of the source. Non‐celebrity advertising appeals were more closely associated with brain activation of regions thought to mediate self‐reflection and also engaging executive functions. For rational advertising appeals, our findings showed significant activation in brain areas associated with logical evaluative decision making reflecting more logical processing value assessments and reward potential. Therefore, retailers/marketers must be particularly mindful to match the appropriate advertising appeal to the specific purpose of the advertisement. This study also provides brain‐based insight into the effectiveness of different types of advertising appeals and whether or not they have the desired impact on the consumer. Copyright © 2016 John Wiley & Sons, Ltd.